Demokrasi dan Amerika Serikat - Muhammad Nasir Badu (Magister Ilmu Politik Universitas Hasanuddin, 2015)
Abstract : The United State of America life is always the result of interaction between the anti-democratic and nondemocratic traditions with the existing democratic traditions, and a new perception in the field of human social, religious, political necessity and political rights. While in Islamic history there are a number of concepts and images that make up a very important Islamic perception of democracy is of course different from what is believed to be in the United State of America.Keywords: Democracy, Islam and United State of America